2023
DOI: 10.1002/ana.26641
|View full text |Cite
|
Sign up to set email alerts
|

Suvorexant Acutely Decreases Tau Phosphorylation and Aβ in the Human CNS

Abstract: Objective In Alzheimer's disease, hyperphosphorylated tau is associated with formation of insoluble paired helical filaments that aggregate as neurofibrillary tau tangles and are associated with neuronal loss and cognitive symptoms. Dual orexin receptor antagonists decrease soluble amyloid‐β levels and amyloid plaques in mouse models overexpressing amyloid‐β, but have not been reported to affect tau phosphorylation. In this randomized controlled trial, we tested the acute effect of suvorexant, a dual orexin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…We thank Dr Kawada for his letter about our recent publication. 1 Our paper found that a dual orexin receptor antagonist, suvorexant, acutely decreased amyloid-β concentrations and the ratio of phosphorylated-tau-threonine-181 to unphosphorylatedtau-threonine-181 (pT181/T181) compared with placebo. We hypothesized that increased sleep from suvorexant would decrease Alzheimer's disease (AD) biomarkers, but there were no significant group differences in total sleep time, sleep efficiency, or time in different sleep stages.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…We thank Dr Kawada for his letter about our recent publication. 1 Our paper found that a dual orexin receptor antagonist, suvorexant, acutely decreased amyloid-β concentrations and the ratio of phosphorylated-tau-threonine-181 to unphosphorylatedtau-threonine-181 (pT181/T181) compared with placebo. We hypothesized that increased sleep from suvorexant would decrease Alzheimer's disease (AD) biomarkers, but there were no significant group differences in total sleep time, sleep efficiency, or time in different sleep stages.…”
mentioning
confidence: 81%
“…
Lucey et al conducted a randomized controlled trial to evaluate the acute effect of suvorexant on amyloid-β, tau, and phospho-tau in the cerebrospinal fluid. 1 The ratio of phosphorylated-tau-threonine-181 to unphosphorylated-tau-threonine-181 significantly decreased in participants treated with suvorexant 20 mg compared with placebo. In addition, amyloid-β also significantly decreased in participants treated with suvorexant after 5 hours of administration.
…”
mentioning
confidence: 94%
“…Finally, individual mechanisms of the hypnotics should be considered. In recent study, suvorexant, the dual receptor antagonist of orexin, which is a wake-promoting neuropeptide recently known to be associated with AD pathology, acutely decreased tau phosphorylation [ 50 ]. Considering a diverse receptor profile involved in each hypnotics and its association will be critical in future research on the association between hypnotics and dementia.…”
Section: Limitation and Future Considerations For The Research On Hyp...mentioning
confidence: 99%
“…In recent study, suvorexant, the dual receptor antagonist of orexin, which is a wake-promoting neuropeptide recently known to be associated with AD pathology, acutely decreased tau phosphorylation. 50 Considering a diverse receptor profile involved in each hypnotics and its association will be critical in future research on the association between hypnotics and dementia. Despite the various limitations mentioned above, there are still many conflicting opinions on the relationship between hypnotics and dementia.…”
Section: Limitation and Future Considerations For The Research On Hyp...mentioning
confidence: 99%
“…Suvorexant binds orexin, a neuropeptide that promotes wakefulness and may be of benefit for insomnia in patients with Alzheimer's (Herring et al, 2020 ). Interestingly, suvorexant also reduces the level of p-tau and Aβ (Lucey et al, 2023 ). Purely anticholinergic medications such as diphenhydramine and all benzodiazepines should be avoided for treating agitation and insomnia.…”
Section: Off-label Neuromodulation: Transcranial Magnetic Stimulation...mentioning
confidence: 99%